2022
DOI: 10.3390/molecules27134108
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Ability of Enhancer RNAs in Metastasis of Non-Small Cell Lung Cancer

Abstract: (1) Background: Non-small cell lung cancer (NSCLC) is the most common lung cancer. Enhancer RNA (eRNA) has potential utility in the diagnosis, prognosis and treatment of cancer, but the role of eRNAs in NSCLC metastasis is not clear; (2) Methods: Differentially expressed transcription factors (DETFs), enhancer RNAs (DEEs), and target genes (DETGs) between primary NSCLC and metastatic NSCLC were identified. Prognostic DEEs (PDEEs) were screened by Cox regression analyses and a predicting model for metastatic NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…As a xenobiotics metabolism enzyme, CYP4B1 has various biological roles. The CYP4B1 mRNA level is low in LUAD and even lower in LUAD at advanced clinical stages ( 65 , 66 ). In lung cancer, TMEM125 and IRX2 have been studied less extensively.…”
Section: Discussionmentioning
confidence: 99%
“…As a xenobiotics metabolism enzyme, CYP4B1 has various biological roles. The CYP4B1 mRNA level is low in LUAD and even lower in LUAD at advanced clinical stages ( 65 , 66 ). In lung cancer, TMEM125 and IRX2 have been studied less extensively.…”
Section: Discussionmentioning
confidence: 99%
“…The KEGG database was used for pathway enrichment analysis of these DEGs in an effort to gain high-level insights into their potential functional relevance. GO enrichment analyses were conducted to assess the enrichment of these DEGs in specific biological processes, molecular functions, and cell components (BPs, MFs, and CCs, respectively) (Liu et al, 2022).…”
Section: Functional Enrichment Analysismentioning
confidence: 99%
“…High expression levels of CYP4B1 in the lungs and its known protoxin bioactivation capabilities generated hypotheses that the enzyme might be associated with lung cancer, and several studies on this topic have been published [103][104][105][106]. In addition, the genetic polymorphism of carcinogen-metabolizing enzymes is suggested to modify an individual's susceptibility to lung cancer.…”
Section: Tissue Distribution Of Cyp4b1 Single Nucleotide Polymorphism...mentioning
confidence: 99%
“…However, no hCYP4B1 genotypes were associated with lung cancer risk; thus, genotype as well as allele frequencies showed no significant difference between the control group and cancer cases [107]. Strikingly, based on data from the Cancer Genome Atlas (TCGA) project and the Gene Expression Omnibus (GEO) database, analysis of hCYP4B1 expression in patients with lung adenocarcinoma (LUAD) showed that hCYP4B1 mRNA expression was significantly reduced in patients with LUAD [104,106]. Additionally, decreased hCYP4B1 expression was more frequently observed in patients younger than 65 years, those with a history of pharmaceutical or radiation therapy, showing mutations in signaling pathways including mutations KRAS, EGFR, or ALK, and with death [105].…”
Section: Tissue Distribution Of Cyp4b1 Single Nucleotide Polymorphism...mentioning
confidence: 99%